STUDI PRODUK HALAL DAGING AYAM POTONG DENGAN PENDEKATAN RANTAI PASOK (SUPPLY CHAIN) DI MAKASSAR - Aslan Risyaldi; Muhammad Nusran; Dirgahayu Lantara (Universitas Mathla’ul Anwar Banten, 2021)
Supply Chain is a concept and regulatory system related to product flow, information flow and financial flows. Activities in the supply chain for broilers consist of the process of raising chicken products by breeders, then processing them into chicken meat that is ready to be marketed from breeders to consumers. The purpose of this study was to analyze the supply chain for chicken meat products and to determine the availability of chickens in the Chicken Slaughterhouse and the availability of chickens in the city of Makassar. Data collection methods are carried out by observation and interviews. Data processing with the preparation of problems in a hierarchy, Validity and Reliability Examiners, Supply chain mapping and hierarchical determination, Calculation of the actual value of each matrix, Inserting weights into the decision matrix, Calculating the normalization value . Data analysis that has been collected is then processed using the Supply Chain Operations Reference (SCOR) method. Of the 15 sub-districts in Makassar city, there are 4 sub-districts which are slaughter centers namely Tamalate (97,643), Manggala (100,762), Biringkanaya (999,554) and Tamalanrea (88,895). where 3 districts are directly adjacent to the buffer area for chicken products, namely Maros and Gowa. The potential supply of chickens to Makassar city will be even greater along with the demand for chicken meat protein. The conclusion is the supply chain channel for chicken products with 3 alternatives, starting from livestock producers, collecting traders, retailers, consumers, then the second alternative is starting from producers, collecting traders and consumers. And the third alternative is starting from the cage, basket, slaughterhouse and consumers.